Unraveling a mysterious skin eruption in a case of Down syndrome - Saikumar, Sanjana; Thankappan, T. P.; Balachandran, P. K.; Thankappan, Asha; Shihabudeen, Shabna; Kanichai, Antony P. (International Journal of Research in Dermatology, 2023)
Collagenoma, also known as collagen naevus, is a connective tissue hamartoma which manifests as a single or localized group of fibrous dermal papules and plaques on the skin, and is characterized by increase in dermal collagen with normal or reduced elastin on histopathology. Cases have been reported in Down syndrome, as isolated or localized lesions, and were presumed to be due to altered free radical metabolism by the enzyme superoxide dismutase, its gene being located on chromosome 21. However, eruptive collagenoma in Down syndrome patients are rarely reported. We present a 22-year-old male Down syndrome patient with asymptomatic eruption of skin lesions on trunk and upper extremities since the past 18 months. He was offered surgical and laser therapy, but at his request, we kept him on regular follow-up.